Improving the Understanding of Reading Rhythm and Notes in Music Education by Using Kodály and Suzuki Technique Method in Grade 8 Junior High School XYZ - Khoe Yao Tung; Nugraha Gusti Satya (Journal on Education, 2023)
The basic or elementary music theory is one of the knowledge that one should masters in playing music. the most common thing, which occurs in students of Arts and Culture subjects (Music) with keyboard musical instrument interest, is a low level of understanding in reading and playing rhythm as well as reading notes in general. Students of grade 8 with keyboard musical instruments interest also have issues with their knowledge regarding basic music theory, especially on reading rhythm and notes. The purpose of this research is to find out methods to improve students' understanding of reading rhythm and notes in a short period. this research consists of three cycles. On each cycle, the researcher uses techniques derived from Kodály and Suzuki's teaching method. Instruments used in this research are observation sheets, rubrics, tests, and student interviews. The result of the activities conducted in the class following this research shows techniques derived from Kodály and Suzuki's teaching method could help improve students' understanding of reading and playing rhythm as well as improving understanding of reading notes. Students of grade 8 with keyboard musical interest experience quite significant understanding improvement and have been helped with reading rhythm and music notation.